The Boundary Theory of Phase Diagrams and Its Application Rules for Phase Diagram Construction with Phase Regions and Their Boundaries - Zhao, Muyu.; Song, Lizhu; Fan, Xiaobao; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The Boundary Theory of Phase Diagrams and Its Application -- Rules for Phase Diagram Construction with Phase Regions and Their Boundaries presents a novel theory of phase diagrams. Thoroughly revised on the basis of the Chinese edition and rigorously reviewed, this book inspects the general feature and structure of phase diagrams, and reveals that there exist actually two categories of boundaries. This innovative boundary theory has solved many difficulties in understanding phase diagrams, and also finds its application in constructing multi-component phase diagrams or in calculating high-pressure phase diagrams. Researchers and engineers as well as graduate students in the areas of chemistry, metallurgy and materials science will benefit from this book. Prof. Muyu Zhao was the recipient of the 1998 Prize for Progress in Science and Technology (for his work on the boundary theory of phase diagrams) awarded by the National Commission of Education, China, and many other prizes.
Part One: The Phase Rule and Its Application -- The phase rule and its application -- Part Two: The Boundary Theory of Isobaric Phase Diagrams and Its Application -- The boundary theory of isobaric phase diagrams -- rules for phase diagram construction -- Application of the boundary theory to unary, binary and ternary phase diagrams and the comparison between the boundary theory and the contact rule -- The application of the boundary theory of phase diagrams to quaternary and higher number component phase diagrams -- The boundary theory in construction of multicomponent isothermal sections -- The boundary theory of isobaric isopleth sections -- Application of boundary theory to isobaric phase diagrams -- Part Three: The Boundary Theory and Calculation of High-Pressure Phase Diagrams -- The boundary theory of p-T-xi multicomponent phase diagrams -- The Calculation of unary and binary high-pressure phase diagrams -- Calculation of high-pressure ternary phase diagrams.
Keywords: Chemistry; Chemistry, Physical organic; Materials; Surfaces (Physics).; Chemistry; Physical Chemistry; Characterization and Evaluation of Materials; Metallic Materials